Macro and micronutrients accumulation in radish (Raphanus sativus L.) subjected to potassium (K) fertilization - Gouveia, Aline Mendes de Sousa [UNESP]; Corrêa, Carla Verônica [UNESP]; Silva, Marcelo de Souza [UNESP]; de Mendonça, Veridiana Zocoler [UNESP]; Jorge, Letícia Galhardo [UNESP]; Martins, Bruno Novaes Menezes [UNESP]; Evangelista, Regina Marta [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP] (Southern Cross Publishing, 2018)
The current study aims to evaluate the effects of potassium fertilization on yield, root quality, macro and micronutrients accumulation in radish production. The experiment was conducted using a randomized block design with five treatments consisted of potassium (K 2 O) topdressing (0, 22.5, 45, 67.5 and 90 kg ha -1 ) applied in the form of potassium chloride and five repetitions. Plants vegetative characteristics, yield, macro and micronutrient accumulation were evaluated in both roots and shoots. Results indicated that K 2 O increased plant height (21.5 cm) at 90 kg ha -1 ; in addition to root fresh mass (40.4 g), total fresh mass (115.2 g), yield (33.7 t ha -1 ), Mg concentration in roots (2.9mg plant -1 ) and B in leaves (3.6 mg plant -1 ), being the best dose for this crop. The decreasing orders of macro and micronutrient accumulation in the shoots were N > P > K > Ca > S > Mg and Fe > Zn > Mn > Cu > B, respectively. The decreasing orders of macro and micronutrient accumulation in the roots were: K > P > N > Ca > S > Mg and Fe > Zn > Mn > Cu > B, respectively.
Keywords: Brassicaceae; Doses of potassium; Nutrition; Productivity; Raphanus sativus L.